Prevalence and factors associated with hyperglycemia in a rural population of Tanvè and Dékanmey in Benin in 2019 - Nicolas Hamondji Amegan; Ariyoh Salmane Amidou; Corine Yessito Houehanou; Helene Robin; Gwladys Nadia Gbaguidi; Corine Agathe Lucresse Fassinou; Kuassi Daniel Amoussou-Guenou; Pierre-Marie Preux; Philippe Lacroix; Stephan Dismand Houinato (Public Library of Science (PLoS), 2022)
Background Hyperglycemia leads to serious damage to the body, especially the blood vessels and nerves. This study aimed to determine the prevalence and factors associated with hyperglycemia in a rural population of Tanvè and Dékanmey in Benin in 2019. Materials and methods This was a cross-sectional, descriptive and analytical study, nested in the Tanvè Health Study (TAHES) cohort. It covered all residents of the villages of Tanvè and Dékanmey, aged 25 years and above, and having given their written consent. Data were collected in the households during the fourth annual monitoring visit in 2019 using the WHO STEPS Wise approach. Hyperglycemia was defined as a fasting capillary blood glucose value ≥ 110 mg/dL. Data were analyzed with R Studio software version 3.5.1. Results A total of 1331 subjects were included in the study with a 60% female predominance and a sex ratio (male/female) of 0.7. The median age was 40 years (Q1 = 32 years; Q3 = 53 years) with a range of 25 and 98 years. The prevalence of hyperglycemia was 4.6%. In multivariate analysis, advanced age (AOR = 1.03; 95%CI = 1.02-1.73; p = 0.004), male sex (AOR = 2.93; 95%CI = 1.49-5.84; p = 0.023), monthly income> 105,000 FCFA (AOR = 2.63; 95%CI = 1.24-5.63; p = 0.030), abdominal obesity (AOR = 2.80; 95%CI = 1.29-6.16; p = 0.007, and obesity (AOR = 1.68; 95%CI = 0.75-3.59; p = 0.004) were statistically associated with hyperglycemia. Conclusion The prevalence of hyperglycemia is not negligible in rural areas in Benin. Our study found that older age, male gender, high income, abdominal obesity, and obesity are determining factors in its occurrence.